The Role of Communication in Organizational Conflict Management at PT. Sinar Makmur Nusa Tenggara - Yovita Marsha Listyono (MediaTor (Jurnal Komunikasi), 2020)
The sales team of PT. Sinar Makmur Timur, Nusa Tenggara area was formed in May 2019 and has been by the company standards in October 2019. In January 2020, the first conflict arose with the absence of the Sales Division during the morning briefing. Then the other conflicts have sprung up between the Sales Division and Area Sales Manager. This research focuses on the role of communication in organizational conflict management, especially the conflict between the Area Sales Manager and the Sales Division at PT. Sinar Makmur Timur Nusa Tenggara area. The approach to this research is a qualitative approach with a case study method. The results insulted that (1) the conflict is caused by the Sales Division which didn’t implement the Standard Operating Procedure (SOP). (2) The conflict resolution uses the team management style from R. Blake & Mouton, the collaborative style from Thomas & Kilmann conflict management, and the integrative negotiation. (3) Communication plays a role in conflict management at PT. Sinar Makmur Timur Nusa Tenggara as the conflict itself as well as a means of conflict resolution. (4) The organizational communication approach in PT. The Sinar Makmur Timur Nusa Tenggara area is a classic approach.